LAW, LITERATURE, AND LEGAL EDUCATION:INNOVATION AND AMBITIONS IN BLACKSTONE’S COMMENTARIES - NICOLINI, Matteo (RIDP REVISTA INTERNACIONAL DE DERECHO PÚBLICO - ISSN 2954-3924, 2021)
The essay explores the relations between legal change and legal education in an attempt to shed new light on the first common-law law textbook, William Blackstone’s Commentaries on the Laws of England. When it comes to examining the rise of the primer as a new legal textual genre, however, the potential of comparative law, in general, and of law and humanities, in particular, is scarcely employed. Scholars usually focus on Blackstone’s influence on the evolution of common-law institutions and legal literature, without ascertaining how eighteenth-century England influenced the structure and contents of the Commentaries. The essay delivers a multidisciplinary assessment of Blackstone’s Commentaries by exploring the educative ambitions of comparative law. Such an assessment is undoubtedly facilitated by the Commentaries, whereby Blackstone triggered noticeable changes in the contents, form, and language of legal education.